Development and Evaluation of an Activity Model for Novice Teacher Development in the Teacher Production for Local Development Project - Phongsophon, Chirawut; Choicharoen, Thapana; Suttiwan, Witsanu; Somsamran, Suchawadee (Journal for Developing the Social and Community, 2026)
Background and Aims: This research aimed to: (1) develop an activity model for enhancing novice teachers participating in the Induction Program (Cohort 8) under the Teacher Production for Local Development Project; (2) evaluate the appropriateness of the developed activity model and (3) synthesize recommendations for improving the Induction Program to meet the long-term professional development needs of novice teachers. Methodology: The target group consisted of 72 novice teachers from nine provinces in the Upper Central Region of Thailand who participated in the program during 26–28 February 2025 at Valaya Alongkorn Rajabhat University under the Royal Patronage. The research instruments included a document analysis form, a participant opinion questionnaire, and reflection notes. The data were analyzed using descriptive statistics, including mean and standard deviation, and qualitative content analysis. Results: The findings revealed that: (1) the developed activity model for novice teacher development consisted of four main components: (a) professional identity and teacher ethics development, (b) instructional competency and innovation enhancement, (c) collaborative learning through Professional Learning Communities and reflective practice, and (d) continuous professional growth linked to professional advancement. The core activities emphasized competency-based instruction (CBL), educational technology and AI integration, classroom action research, inclusive education, and individual development planning. (2) The overall appropriateness of the activity model was rated at a high level (𝑥̄ = 4.42, SD = 0.52), indicating its suitability in terms of content, learning process, and practical applicability in school contexts. (3) The synthesized recommendations highlighted the need to improve time management and the structure of training sessions, reduce the density of activities, expand opportunities for professional collaboration among participants, and add topics relevant to 21st-century teacher competencies, such as instructional coaching, positive teacher psychology, and classroom innovation. Additionally, it was recommended that a post-training support system be implemented through online PLCs or mentoring to ensure sustainable teacher development. Conclusion: The activity Model for Novice Teacher Development in the Teacher Production for Local Development was rated as highly appropriate (or highly satisfactory). Recommendations include revising the training schedule structure, reducing the density of activities, and incorporating professional topics essential for the 21st century.